Sex differences in metabolic disorder patterns of first-episode drug-naive patients with schizophrenia. (February 2021) - Zhou, Yongjie; Song, Xinxin; Guo, Yanhong; Lang, Xiaoe; Li, Zezhi; Zhang, Xiang Yang
Highlights: There was a sex difference in the prevalence of metabolic disturbance patterns of first-episode drug-naive schizophrenia. There was a sex difference in the association between metabolic parameters and psychopathological symptoms. Abstract: Although metabolic disorders are common in schizophrenia, few studies investigated sex differences in metabolic disorder. This study aimed to examine the sex differences in the clinical correlates of metabolic disorders and MetS in patients with first-episode drug-naïve (FEDN) schizophrenia. A total of 257 FEDN schizophrenia patients and 118 controls were recruited. Body mass index (BMI), waist circumference (WC) and blood pressure were measured. Fasting blood samples were drawn to detect triglycerides, cholesterol, high density lipoprotein cholesterol (HDLC), low density lipoprotein cholesterol (LDLC), blood glucose, glycosylated hemoglobin (HbA1c) and insulin. The Positive and Negative Syndrome Scale (PANSS) was applied to assess the clinical symptoms. There was sex difference in the prevalence of high BMI and dyslipidemia of schizophrenia patients. Female patients had lower prevalence of high BMI (p = 0.03) and hypertriglyceridemia (p = 0.006), but had higher prevalence of hypo-HDLC (p = 0.005), compared with male patients. Further, there were sex differences in the relationship between metabolic parameters and psychopathological dimensions. In male patients, WC was associated with positive symptoms and negative symptoms (r = 0.26, p Bonferroni = 0.02; r = 0.26, p Bonferroni = 0.02). In female patients, BMI (r = 0.26, p Bonferroni = 0.01), WC (r = 0.30, p Bonferroni = 0.004) and HAb1c were associated with positive symptoms (r = 0.27, p Bonferroni = 0.008). Insulin (r = 0.24, p Bonferroni = 0.02; r = 0.23, p Bonferroni = 0.04) and HOMA-IR (r = 0.29, p Bonferroni = 0.004; r = 0.25, p Bonferroni = 0.02) were associated with positive symptoms and general psychopathology symptoms. The contribution of clinical and metabolic components to MetS was almost same between male and female patients. Our study demonstrates sex difference in metabolic disorder patterns in schizophrenia patients.